1997
DOI: 10.1074/jbc.272.45.28732
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of AUUUA Response Element Binding by Heterogeneous Nuclear Ribonucleoprotein A1 in Human T Lymphocytes

Abstract: The heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) shuttles between the cytoplasm and nucleus and plays important roles in RNA metabolism. Whereas nuclear hnRNP A1 has been shown to bind intronic sequences and modulate splicing, cytoplasmic hnRNP A1 is associated with poly(A) ؉ RNA, indicating different RNA ligand specificity. Previous studies indicated that cytoplasmic hnRNP A1 is capable of high-affinity binding of reiterated AUUUA sequences (ARE) that have been shown to modulate mRNA turnover and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 69 publications
3
94
0
Order By: Relevance
“…Although stimulation of these signalling pathways markedly increased reporter gene expression in cells expressing GAL4-hnRNP D0 (Table 1), stimulation increased reporter gene expression of control samples as well. Protein kinase C, protein kinase A and casein kinase II phosphorylate hnRNP A1 in itro, and it has been shown that its phosphorylation state affects its ability to interact with RNA [34,35]. hnRNP A2 is also phosphorylated by casein kinase II [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although stimulation of these signalling pathways markedly increased reporter gene expression in cells expressing GAL4-hnRNP D0 (Table 1), stimulation increased reporter gene expression of control samples as well. Protein kinase C, protein kinase A and casein kinase II phosphorylate hnRNP A1 in itro, and it has been shown that its phosphorylation state affects its ability to interact with RNA [34,35]. hnRNP A2 is also phosphorylated by casein kinase II [36].…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic preparations were performed as previously described using a method characterized for its lack of contamination by nuclear proteins (22,27). For immunoblotting, cytoplasmic and gradient fractions were boiled in loading buffer (50 mM Tris-HCl (pH 6.8), 100 mM DTT, 2% SDS, 0.1% bromophenol blue, and 10% glycerol) for 3 min, resolved by 12 or 8 -16% SDS-PAGE, and then electrotransferred to nitrocellulose.…”
Section: Immunoblottingmentioning
confidence: 99%
“…What enables hnRNP A1 to have such broad functions in RNA metabolism is its ability to bind both nuclear and cytoplasmic RNAs (10). In addition to its well characterized role in nuclear RNA processing, hnRNP A1 binds to purine-rich sequences of mRNAs for mRNA turnover and translation (13,14).…”
mentioning
confidence: 99%
“…The heterogeneous nuclear ribonucleoprotein A1 (hnRNP A1) is a predominantly nuclear protein engaged in a number of cellular and viral RNPs for RNA-processing activities, including splicing regulation, nuclear export, microRNA processing, mRNA stability, telomere maintenance, and IRES-mediated translation initiation (7)(8)(9)(10)(11)(12). What enables hnRNP A1 to have such broad functions in RNA metabolism is its ability to bind both nuclear and cytoplasmic RNAs (10).…”
mentioning
confidence: 99%